1988
DOI: 10.1063/1.340150
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Mn on the positive temperature coefficient of resistance characteristics of donor doped BaTiO3 ceramics

Abstract: BaTiO3 positive temperature coefficient of resistance (PTCR) specimens were made from commercial BaTiO3 which was mixed with 0.35 mol. % of Ho2O3 to make it semiconducting and 0.07 mol. % of MnCO3. After sintering at 1320 °C the samples were annealed in batches at 1220 °C for various periods between 0 and 5 h. The effect of Mn was studied by making direct comparison with previous results obtained from Mn free but otherwise identical specimens. Room-temperature dielectric measurements in the audio and radio fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…22 Thus, during reoxidation N S (T) increases, leading to an associated increase in ϕ 0 (T), according to Eq. (2).…”
Section: Electrical Propertiesmentioning
confidence: 96%
“…22 Thus, during reoxidation N S (T) increases, leading to an associated increase in ϕ 0 (T), according to Eq. (2).…”
Section: Electrical Propertiesmentioning
confidence: 96%
“…However, the Mn addition induces the inverse behavior for breakdown strength of BNBT-KNN ceramics. The reason can be that Mn dopant acts partly as a grain-boundary barrier layer in bulk ceramics as reported in most of PTCR ceramics [22,23]. In suitable composition range of Mn dopant, thus, the grain-boundary barrier height of bulk ceramics will go up with rise of Mn content and leads to the increase of breakdown strength.…”
Section: Introductionmentioning
confidence: 95%
“…It has been reported that the BT-based semicondouting, not semicondouting ceramics sintered in a reducing atmosphere show a clear PTC property after annealing in air. [12][13][14] Hence the as-sintered semiconducting samples, BBKT5 ceramics sintered at 1350 • C in a N 2 flow with low O 2 concentration were annealed in air at various soaking temperatures and times. Fig.…”
Section: Resultsmentioning
confidence: 99%